(untitled) (Metallurgy and Foundry Engineering, 2013)
Statistical methods belong to the basic quality tools. Among statistical instruments the statistical process control SPC takes particular place. One of the principal tasks of SPC is process capability analysis i.e. the assessment of process potential as for variability regarding expectations defined by specification limits. This work concerns the comparative analysis of capability indices determination in case of distribution unlike the normal one.